2022
DOI: 10.1111/nph.17935
|View full text |Cite
|
Sign up to set email alerts
|

In planta vs viral expression of HCPro affects its binding of nonplant 21–22 nucleotide small RNAs, but not its preference for 5′‐terminal adenines, or its effects on small RNA methylation

Abstract: Summary Previous studies have found a correlation between the abilities of PVX vector‐expressed HCPro variants to bind small RNAs (sRNAs), and to suppress silencing. Moreover, HCPro preferred to bind viral sRNAs of 21–22 nucleotides (nt) containing 5′‐terminal adenines. This would require such viral sRNAs to have either different access to the suppressor than those of plant sequences, or different molecular properties. To investigate this preference further, we have used suppressor‐competent or suppressor‐de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Functional redundancy of Potyviridae noncore modules was previously observed (Pasin et al, 2022), and it remains to be determined if, besides AlkB, other potyviral proteins regulate the balance of internal RNA modifications. Of note, HC-Pro of potyviruses interferes with small RNA 3′ end methylation (Del Toro et al, 2022;Yu et al, 2006) and interacts or colocalizes with RNA decay components that are linked to the activity of plant ALKBH9 homologues (De et al, 2020;Li & Wang, 2018;Martínez-Pérez et al, 2017). The interplay of RNA methylation and m 6 A with known plant antiviral systems including RNA silencing and decay, small molecule signalling, and resistance gene pathways deserves further investigation.…”
Section: Slippage Of the Potyvirus Replicase Causes Frameshifting In ...mentioning
confidence: 98%
“…Functional redundancy of Potyviridae noncore modules was previously observed (Pasin et al, 2022), and it remains to be determined if, besides AlkB, other potyviral proteins regulate the balance of internal RNA modifications. Of note, HC-Pro of potyviruses interferes with small RNA 3′ end methylation (Del Toro et al, 2022;Yu et al, 2006) and interacts or colocalizes with RNA decay components that are linked to the activity of plant ALKBH9 homologues (De et al, 2020;Li & Wang, 2018;Martínez-Pérez et al, 2017). The interplay of RNA methylation and m 6 A with known plant antiviral systems including RNA silencing and decay, small molecule signalling, and resistance gene pathways deserves further investigation.…”
Section: Slippage Of the Potyvirus Replicase Causes Frameshifting In ...mentioning
confidence: 98%
“…In previous works, we had found that systemic accumulation of chimera 1 was significantly higher in DCL2/4.5i transgenic N. benthamiana plants, which have reduced levels of 21 and 22 nucleotide (nt) sRNAs and the silencing defences mediated by DCL2 and 4 compromised, compared to WT plants (del Toro et al., 2022 ). Thus, we tested the accumulation of the four viral chimeras in these transgenic plants.…”
Section: Resultsmentioning
confidence: 98%
“…In a previous work, we created a PPV/PVY chimera as a tool for studies on PVY HCPro suppression of silencing function (del Toro et al., 2022 ). Compared to the parental PPV–GFP, the chimera accumulated and moved poorly (Sun et al., 2022 ), but after several mechanical passages it increased in virulence (titres, symptoms, speed of infection) in some plants.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of HC-Pro to bind to nucleic acids has been experimentally shown via oligo(dT) purification [30,31]. More recently, HC-Pro was found to preferentially bind to viral sRNAs with 21-22 nucleotides containing 5′-terminal adenines, thereby suppressing silencing [32]. In green, KITC and PTK are required for aphid transmission.…”
Section: Hc-pro Is a Multifunctional Proteinmentioning
confidence: 99%